Purity analysis of hydrogen cyanide, cyanogen chloride and phosgene by quantitative (13)C NMR spectroscopy - Henderson, Terry J (Magnetic resonance in chemistry : MRC, 2007)
Hydrogen cyanide, cyanogen chloride and phosgene are produced in tremendously large quantities today by the chemical industry. The compounds are also particularly attractive to foreign states and terrorists seeking an inexpensive mass-destruction capability. Along with contemporary warfare agents, therefore, the US Army evaluates protective equipment used by warfighters and domestic emergency responders against the compounds, and requires their certification at > or = 95 carbon atom % before use. We have investigated the (13)C spin-lattice relaxation behavior of the compounds to develop a quantitative NMR method for characterizing chemical lots supplied to the Army. Behavior was assessed at 75 and 126 MHz for temperatures between 5 and 15 degrees C to hold the compounds in their liquid states, dramatically improving detection sensitivity. T(1) values for cyanogen chloride and phosgene were somewhat comparable, ranging between 20 and 31 s. Hydrogen cyanide values were significantly shorter at 10-18 s, most likely because of a (1)H--(13)C dipolar contribution to relaxation not possible for the other compounds. The T(1) measurements were used to derive relaxation delays for collecting the quantitative (13)C data sets. At 126 MHz, only a single data acquisition with a cryogenic probehead gave a signal-to-noise ratio exceeding that necessary for certifying the compounds at > or = 95 carbon atom % and 99% confidence. Data acquired at 75 MHz with a conventional probehead, however, required > or = 5 acquisitions to reach this certifying signal-to-noise ratio for phosgene, and >/= 12 acquisitions were required for the other compounds under these same conditions. In terms of accuracy and execution time, the NMR method rivals typical chromatographic methods